Novel 2-Thiazolylhydrazone with Druggable Properties for Antifungal Application - Wallace Cordeiro de Morais; Gustavo Henrique Oliveira Costa; Vinícius Leal Pitcella; João Victor Vanolli Protti; Carolina Paula de Souza Moreira; José Eduardo Gonçalves; Susana Johann; Renata Barbosa de Oliveira (Journal of Fungi)
Fungal infections have become a growing concern in healthcare, particularly in immunocompromised individuals, with species like Candida, Cryptococcus, and Sporothrix posing significant challenges due to rising resistance and limited treatment options. In response, novel antifungal agents are being explored, including thiazolyl hydrazones. This study focuses on the development of a novel thiazolylhydrazone derivative, RW3. RW3 was synthesized to improve its water solubility and pharmacokinetic properties. The compound demonstrated a broad antifungal spectrum, particularly effective against Cryptococcus neoformans and Candida auris, with minimal irritant potential and low cytotoxicity. RW3 showed favorable solubility and high intestinal permeability, indicating potential for oral administration. The results suggest RW3 as a promising lead for further development as a therapeutic agent for systemic fungal infections. These findings underscore the importance of optimizing drug properties to enhance efficacy and safety profiles, opening the path for the development of innovative antifungal treatments.